Proceedings of 1995 IEEE International Conference on Robotics and Automation
DOI: 10.1109/robot.1995.526021
|View full text |Cite
|
Sign up to set email alerts
|

Development in underwater robotics

Abstract: This paper is written as a survey paper summarizing the current state-of-the-art and discussing future research directions in the area of Underwater Robotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In order to describe the motion of an underwater robotic vehicle (URV), we assume the notation of The Society of Naval Architects and Marine Engineers (SNAME). [32][33][34][35][36][37][38] Specifically, as represented in Fig. 1, we assume a body-fixed coordinate system with the origin located at the vehicle's center of buoyancy, which is assumed to be constant with respect to the vehicle since we are not considering possible changes in shapes or volumes.…”
Section: Coordinate Systemmentioning
confidence: 99%
“…In order to describe the motion of an underwater robotic vehicle (URV), we assume the notation of The Society of Naval Architects and Marine Engineers (SNAME). [32][33][34][35][36][37][38] Specifically, as represented in Fig. 1, we assume a body-fixed coordinate system with the origin located at the vehicle's center of buoyancy, which is assumed to be constant with respect to the vehicle since we are not considering possible changes in shapes or volumes.…”
Section: Coordinate Systemmentioning
confidence: 99%
“…Some very interesting talks Corporations ( h t t p : //bluef i n r o b o t i c s . COD) develabout state of the art and direction of the underwaoped, in collaboration with MIT, different AUVs, ter robotics have been given, e.g., in (Yuh, 1995; such as Bluefin 21, for deep operations up to 4500111;and West, 2001;Ura, 2003;Yuh, 2003). At the best C&C technologies (www.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that highly dextrous underwater manipulator systems are critical to the development of self-contained autonomous underwater vehicles (Yuh 1995).…”
Section: Introductionmentioning
confidence: 99%